Multi-faceted elastic flexibility of 1-naphthyl and 9-anthryl 2, 2′:6′, 2′′-terpyridine crystals. Issue 47 (16th November 2022) - Kusumoto, Sotaro; Oishi, Karin; Nakaya, Manabu; Suzuki, Ryo; Tachibana, Masaru; Kim, Yang; Koide, Yoshihiro; Hayami, Shinya
Abstract : We report two organic crystals of 2, 2′:6′, 2′′-terpyridine derivatives each substituted with luminescent naphthyl and anthryl moieties, displaying multi-faceted flexible bending with elasticity in response to mechanical stress. Abstract : Functional molecular crystals capable of multidirectional deformation by external stimuli have the potential to be used in various applications such as mechanosensors and flexible devices. We report two organic crystals of 2, 2′:6′, 2′′-terpyridine derivatives each substituted with luminescent naphthyl (1 ) and anthryl (2 ) moieties, displaying multi-faceted flexible bending with elasticity in response to mechanical stress, whose properties are evaluated in detail using their nanoindentations, single crystal X-ray structure analyses, and energy frame calculations.